Detection of Quantitative Trait Loci Controlling the Content of Phenolic Compounds in an Asian Plum (Prunus salicina L.) F1 Population - Valderrama-Soto, Diego; Salazar, Juan; Sepúlveda-González, Ailynne; Silva-Andrade, Claudia; Gardana, Claudio; Morales, Héctor; Battistoni, Benjamin; Jiménez-Muñoz, Pablo; González, Mauricio; Peña-Neira, Álvaro; Infante, Rodrigo; Pacheco, Igor (Frontiers in Plant Science, 2021)
Consumption of fresh fruit is known to protect against non-communicable diseases due to the fruits content in compounds with an antioxidant capacity, among them, polyphenols. Asian plums (Prunus salicina L.) accumulate more than 40 phenolic compounds, with a remarkable diversity in their profiles, depending on the variety and environmental conditions. Although candidate genes have been indicated to control this trait, the loci controlling its phenotypic variation have not yet been defined in this species. The aim of this work was to identify the Quantitative Trait Loci (QTL) controlling the phenolic compounds content in the Asian plum skin and flesh. Using UHPLC-DAD-Orbitrap-MS, we determined that cyanidin-3-glucoside and cyanidin-3-rutinoside are the main anthocyanins in Asian plums. Other anthocyanins found to a lesser extent were tentatively identified as cyanidin bound to different sugar and procyanidin moieties. Then we phenotyped fruit of 92 and 80 F1 seedlings from the cross <'98.99' x 'Angeleno'> (98Ang) for two harvest seasons. We used HPLC-DAD to quantify single anthocyanin and spectrophotometric techniques to determine the total content of phenols, flavonoids, procyanidins and antioxidant activity (DPPH and FRAP). To determine the phenotype-genotype association of phenolic compounds content, phenotypic values (adjusted by linear mixed-effects models), genotypic data and linkage maps were analyzed with multiple-QTL model (MQM) approach. We found a total of 21 significant trait-marker associations: 13 QTLs segregating from '98.99' and 8 QTLs from 'Angeleno'. From these associations, 8 corresponded to phenolic compound content in the flesh and 13 in the skin. Phenotype variance was explained by the found loci ranging from 12.4% to 27.1%. The found loci are related to the content of cyanidin-3-glucoside (LG4), cyanidin-3-rutinoside (LG4), total flavonoids and procyanidins (LG5 and LG8), and minor anthocyanin compounds (LG3 and LG4). These results will help improve the efficiency of breeding programs for the generation of Asian plum varieties with high phenolic compound content.